Legal factors of employment of seafarers - Iryna Pidpala (Kazimierz Wielki University, 2020)
The article is devoted to the study of legal regulation of the employment of sailors.  Employment is an independent procedure that implies a job acceptance and includes a certain number of actions as a candidate for the post and shipowner. Installed, the specificity of marine hiring requires special conditions and regulation of labor relations, including the norms of domestic legislation and international.  Depending on the position, a certain number of qualified documents that have been checking are established.  Feature when taking a sailor to work Captain's coordination.